Modeling and Optimization to Increase Lecturers' Work Commitment - Wisman Jaya, Herdi; Hardhienata, Soewarto; Suhardi, Eka (International Journal Labs, 2024)
This study aims to find strategies and ways to increase lecturers' work commitment by examining other variables that have a positive and dominant effect on lecturers' work commitment. These variables are self-efficacy, teamwork, compensation, and achievement motivation either directly or indirectly with the variable work commitment of Pamulang University lecturers. The population of this study were 2024 lecturers from 17 study programs from the total lecturers of Pamulang University, South Tangerang in the 2019/2020 academic year based on PDDikti Region IV West Java and Banten data. The sampling technique used proportional sandom sampling with the Cochran Formula with a sample of 267. The results of the study found that 1) there is a direct influence of self-efficacy on lecturer work commitment; 2) There is a direct influence between teamwork on lecturer work commitment; 3) There is a direct influence between compensation on lecturer work commitment; 4) There is a direct influence between achievement motivation on lecturer work commitment; 5) There is a direct influence between self-efficacy on achievement motivation; 6) There is a direct influence between teamwork on achievement motivation; 7) There is a direct influence between compensation on achievement motivation; 8) There is an indirect effect between self-efficacy through achievement motivation on lecturer work commitment; 9) There is an indirect effect between teamwork through achievement motivation on lecturer work commitment; and 10) There is an indirect effect of compensation through achievement motivation on lecturer work commitment. SITOREM results show that there are 14 indicators from 5 variables that need to be improved and 10 indicators from 5 variables that are maintained and developed. This study concludes that strengthening self-efficacy, teamwork, compensation and achievement motivation can increase lecturers' work commitment.